Mining Business Permit (IUP) Regulations & Policies That Provide Legal Certainty and Ease of Investing in the Mining Sector in Indonesia - Wahyudi Siswanto (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
The promulgation of Law Number 23 of 2014 concerning Regional Government, revoked the authority of City/Regency Regional Governments in granting Mining Business Permits (IUP) and henceforth this authority was given by the Central Government to Provincial Governments. However, in practice, the implementation of this policy is still faced with many obstacles, including a lot of overlap in the granting of IUPs before the new policy was adopted. Therefore, it is important to offer a policy model for granting IUPs that provides more legal certainty and makes it easier to invest in the mining sector in Indonesia.